Correct Answer - Option 2 : 3M

^{2}
**Given:**

The mean of a, b, c is M and ab + bc + ca = 0

**Formula used:**

Mean = (Sum of all the terms/Total number of terms)

(a + b + c)^{2} = a^{2} + b^{2} + c^{2} + 2(ab + bc + ca)

**Calculation:**

Mean = (a + b + c)/3 = M

⇒ (a + b + c) = 3M ----(1)

Now, (a + b + c)2 = a2 + b2 + c2 + 2(ab + bc + ca)

⇒ (3M)^{2} = a2 + b2 + c2 + 2 × 0 ----(from eq (1))

⇒ 9M^{2} = a2 + b2 + c^{2} ----(2)

Now, Mean = (a2 + b2 + c2)/3

⇒ (9M^{2})/3 ----(from eq 2)

⇒ 3M2

**∴ The mean of the given expression is 3M2 **